(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from February to June 2018 with a view to study the effect of mulch and organic amendments on growth and yield performance of BRRI dhan58 under dry direct seeded boro rice production system. The experiment included two set of treatments. A. Mulch (M1=rice straw mulch @ 7 t ha-1 and M2=No mulch) and B. Organic amendments (T1=Trico-compost (TC) @ 5 t ha-1, T2 =Farm Yard Manure (FYM) @ 5 t ha-1, T3 =Mustard Oil Cake (MOC) @ 0.5 t ha-1, T4= Trico-compost (TC) @ 5 t ha-1 + Mustard Oil Cake (MOC) @ 0.5 t ha-1, T5 = Farm Yard Manure (FYM) @ 5 t ha-1 + Mustard Oil Cake (MOC) @ 0.5 t ha-1, T6=Control). The experiment was laid out in a split-plot design with mulch in the main plot and organic amendments in the sub-plot. The treatments were replicated three times. The higher plant height (95.90 cm), no. of effective tillers hill-1 (11.48), 1000-grains weight (24.75 g), grain yield (5.34 t ha-1), and straw yield (7.38 t ha1) were found from rice straw mulch plots. The highest plant height (103.40 cm), panicle length (23.24 cm), no. of grain panicle-1 (118.79), 1000-grain weight (25.23 g), grain yield (5.67 t ha-1), straw yield (7.80 t ha-1), biological yield (13.47 t ha-1) and harvest index (42.06%) were found from treatment T4 (Tricho compost+Muatard Oil Cake). The crop grown with recommended rate of fertilizers (T6) gave the worst performance. The interaction between mulch and organic amendments were not significant for grain yield. Thus the study concludes that rice straw mulching gives better yield than no mulch plots and the organic amendment is better than recommended inorganic fertilizer application. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 48-59